Visit by Dr. Mohd Ridzuan bin Darun - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
On Thursday, March 3, 2016, Dr. Mohd Ridzuan bin Darun visited ABEST21 office.